Depressive symptoms and associated factors in elderly people in the Primary Health Care - Rosmarie Hajjar; Giovanna Gaudenci Nardelli; Eliana Maria Gaudenci; Álvaro da Silva Santos (Rev Rene)
Objective: to analyze depressive symptoms and its associated factors, the use of antidepressants and the presence of a diagnosis of depression in the elderly. Methods: cross-sectional study with 248 elderly people attended in Basic Health Units using the Geriatric Depression Scale - Short Form. A chi-square test, the odds ratio and a binary logistic regression were used to analyze the data. Results: depressive symptoms were identified in 32.7% of the elderly, 25.4% with scores indicative of mild depression and 7.3% of severe depression. Physical activity and comorbidities were the factors associated with the presence of depressive symptoms. Among the elderly, 22.2% presented a previous diagnosis of depression and 17.0% of them used antidepressants. Conclusion: depressive symptoms were associated with physical inactivity and comorbidities. Fewer than half of the elderly with indicatives of severe depression used antidepressants. The report of a previous diagnosis of depression was more frequent than the indicatives of severe depression.